Integrating social protection and digital platforms for workforce reintegration of disabled workers: A hexahelix approach - Muhammad Adnan Nurcahyo; Dewinta Iga Wardani; Christian Farold Purba (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: Workers with permanent total disability face high risks of job loss, long-term income insecurity, and social exclusion, while existing social protection in Indonesia remains largely short-term and compensatory. This study examines regulatory and institutional gaps in disability protection, the limitations of Employment Injury and Unemployment Insurance, and explores optimizing the SiapKerja digital platform through cross-sector collaboration to enhance inclusive workforce reintegration. Methods: This study employs a qualitative case study approach focusing on the SiapKerja platform as a central case within the broader context of social protection policies and return-to-work mechanisms. The analysis uses secondary data derived from national regulations, official institutional documents, and relevant academic literature. Data are analyzed using thematic analysis to identify patterns related to policy design, institutional fragmentation, and barriers to workforce reintegration. Findings: The analysis reveals three main challenges: exclusion of workers with permanent total disability from unemployment insurance benefits limits income continuity and access to labor market services; employment injury insurance benefits are predominantly lump-sum and insufficient for long-term economic resilience; and utilization of Return-to-Work programs remains minimal due to weak referral systems, limited adaptive training capacity, and low employer participation. Additionally, SiapKerja has not yet been designed as disability-friendly and lacks integration with accident insurance and Return-to-Work data, reducing its effectiveness as a career reintegration tool. From a public value perspective, fragmented governance and non-inclusive digital design constrain equitable access to skills development and decent work for injured workers with disabilities. Conclusion: An integrated, career-based return-to-work ecosystem is required to shift social protection from passive compensation toward active reintegration. Novelty/Originality of this article: This study proposes a hexahelix collaboration model that integrates social protection data, disability adaptive vocational training, inclusive employers, and an upgraded SiapKerja platform featuring a dedicated disability mode, automatic enrollment, and capability-based job matching supported by progressive employer incentives.